2013
DOI: 10.1155/2013/192573
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Metastasis as an Initial Presentation of Follicular Thyroid Carcinoma: A Case Report and a Review of the Literature

Abstract: Introduction. Follicular thyroid carcinoma (FTC) frequently metastasizes to the lungs and bones. However, metastasis to the skeletal muscles is an extremely rare manifestation of FTC. To date, only seven cases of FTC have been reported in the literature. Skeletal muscle metastases from FTC usually remain asymptomatic or manifest as swelling and are associated with dismal prognosis. Case Presentation. A 45-year-old Saudi woman presented with right buttock swelling since 8 months. Physical examination revealed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…In contrast to the results of Song et al ( 5 ), the present review identified that among the patients with muscle DTC metastasis with a detailed medical history, 1/3 complained of muscle pain, and the metastatic tumor could be detected by palpation in the majority of cases. This finding is in accordance with the statement by Tunio et al that ‘skeletal muscle metastases present as painful masses’ ( 11 ). However, it is difficult to agree with the statement by Xue et al that ‘Most of skeletal muscle metastases are silent and may occasionally present as painful masses’ ( 12 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast to the results of Song et al ( 5 ), the present review identified that among the patients with muscle DTC metastasis with a detailed medical history, 1/3 complained of muscle pain, and the metastatic tumor could be detected by palpation in the majority of cases. This finding is in accordance with the statement by Tunio et al that ‘skeletal muscle metastases present as painful masses’ ( 11 ). However, it is difficult to agree with the statement by Xue et al that ‘Most of skeletal muscle metastases are silent and may occasionally present as painful masses’ ( 12 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, it is difficult to agree with the statement by Xue et al that ‘Most of skeletal muscle metastases are silent and may occasionally present as painful masses’ ( 12 ). The mean size of the metastatic tumors was 6 cm, and this size is similar to that described by Tunio et al (2–12 cm) ( 11 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Some case reports and series have shown that synchronous UM in DTC patients presenting initially with UM-related symptoms, but they have difficulty in finding the primary cancer origin due to unusual metastatic sites [17]. However, the most of UMs from DTC were found to develop metachronously in previous studies [10,12].…”
Section: Plos Onementioning
confidence: 99%
“…While FTC usually remains localized to the thyroid gland, distant metastasis is observed in a minority of patients, with a reported incidence ranging from 4% to 15% (1)(2)(3). Metastatic FTC significantly contributes to disease morbidity and has been found to be associated with a 10-year survival of 40-45% (2).…”
Section: Introductionmentioning
confidence: 99%